Erosion Rate of Lateral Slope Deposit Under the Effects of Different Influencing Factors - Ge, Yonggang; Guo, Xiaojun; Zhan, Meiqiang; Yan, Hua (Frontiers in Earth Science, 2021)
Lateral slope deposit failure represents a major source of material for debris flow/flood formation in headwater regions. From the perspective of inducing factors, such failures are the result of combined action of hydrodynamic and gravitational forces. This work investigated the failure process of a lateral slope soil deposit using indoor flume experiments. The key factors considered were the fine particle content and bulk density of the soil deposit, inflow discharge, and channel slope. Overall, the failure process can be divided into three stages: slope toe erosion stage, frequent failure stage, and gradual stabilization stage. Results revealed that greater bulk density and fine particle content increased erosion difficulty, whereas greater slope meant lower inflow was required to initiate erosion. In addition to the slope deposit failure process, the process of debris flood formation was also investigated and the critical conditions required for debris flood formation were identified. Debris floods occurred only when the fine particle content of the soil deposit was <30 %, they formed more easily when the bulk density was 1.4 and 1.5 g/cm3 than when it was 1.6 and 1.7 g/cm3, and they formed only when the slope was > 7°. Accordingly, a critical runoff condition was proposed by describing the grain composition of the soil using grain size distribution parameters. The findings of this study enhance understanding of the mechanism of debris flow/flood formation, which could help improve debris flood forecasting in headwater regions of mountainous catchments.